Identifikasi Potensi Kelembagaan Pertanian dan Kelembagaan Keuangan di Kabupaten Sukabumi - Eliesa Septiani (Jurnal Agribisnis dan Pembangunan Pertanian (JAPP), 2023)
Identification of institutional potential is the first step to determine the condition and activities of institutions in Sukabumi District, especially in Region 7, namely Tegalbuleud, Cidadap, Cidolog, Sagaranten, Curugkembar, and Pabuaran. The method used in this research is descriptive method. The data obtained is secondary data. The purpose of this research is to identify the potential of institutions in Sukabumi district. The result of this research is that in Sukabumi district there are two types of institutions, namely agricultural institutions and financial institutions. These types of institutions have an active status. So, based on the identification results, it can be concluded that activity and strengthening are factors that need to be developed. Because institutions can be one of the potential instruments that play a role in the process of regional development in Sukabumi District.